How Grade 11 Students Match Audio to Function Graphs: Distractor Patterns and Error Pathways - Parreño, Samuel John; Alleander Kate Gicale, (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
Multiple-choice responses can reveal which graph features guide students’ choices, not only whether an answer is correct. This study examined distractor patterns and pretest-to-posttest error pathways in audio-to-graph matching among 194 Grade 11 students from seven classes in a Philippine public secondary school. Parallel nine-item forms used level-coded audio, in which pitch tracked graph value, and rate-coded audio, in which pitch tracked local change. Responses were classified by correctness, graph family, mapping mismatch, and mathematical error category. Mean scores increased from 2.12 (SD = 1.32) to 3.64 (SD = 1.72) out of 9, W = 1972, p < .001, r = .601. Level-coded tasks showed marked movement from rate-coded lures to correct responses. Rate-coded tasks retained broader patterns of graph-level fallback, constant-versus-changing-rate confusion, concavity confusion, and nonlinear-rate confusion. Across 1,746 paired item attempts, 31.0% moved from incorrect to correct and 28.8% shifted between different incorrect categories. The study contributes a diagnostic pathway approach that identifies which distinctions in graph level, slope, concavity, and changing rate stabilized after instruction and which remained unsettled.